Magnesium diboride sourcebook - Fisher, D. J. (Diffusion and defect data. Defect and diffusion forum, 2006)
This substance is very much a material for the new millennium, since its new manifestation as a high-temperature superconductor can be dated precisely from the seminal 2001 Nature paper (1st March, p63), Superconductivity at 39K in Magnesium Diboride, by J. Nagamatsu, N. Nakagawa, T. Muranaka, Y. Zenitani and J. Akimitsu of the Physics Department of Aoyama-Gakuin University, Tokyo. Until then, it had been seen and used only as a rather nondescript ceramic/abrasive. The current volume is intended to show the full breadth of work which has been done in the relatively short period since its 're-discov.